Squalenoyl siRNA PMP22 nanoparticles are effective in treating mouse models of Charcot-Marie-Tooth disease type 1 A - Boutary, Suzan (Commun Biol, 2021)
Charcot-Marie-Tooth disease type 1 A (CMT1A) lacks an effective treatment. We provide a therapy for CMT1A, based on siRNA conjugated to squalene nanoparticles (siRNA PMP22-SQ NPs). Their administration resulted in normalization of Pmp22 protein levels, restored locomotor activity and electrophysiological parameters in two transgenic CMT1A mouse models with different severity of the disease. Pathological studies demonstrated the regeneration of myelinated axons and myelin compaction, one major step in restoring function of myelin sheaths. The normalization of sciatic nerve Krox20, Sox10 and neurofilament levels reflected the regeneration of both myelin and axons. Importantly, the positive effects of siRNA PMP22-SQ NPs lasted for three weeks, and their renewed administration resulted in full functional recovery. Beyond CMT1A, our findings can be considered as a potent therapeutic strategy for inherited peripheral neuropathies. They provide the proof of concept for a new precision medicine based on the normalization of disease gene expression by siRNA.